The recent landscape of RSV vaccine research - Karen Kelleher; Nadisha Subramaniam; Simon B. Drysdale (Therapeutic Advances in Vaccines and Immunotherapy)
Respiratory syncytial virus (RSV) causes a significant burden of acute respiratory illness across all ages, particularly for infants and older adults. Infants, especially those born prematurely or with underlying health conditions, face a high risk of severe RSV-related lower respiratory tract infections (LRTIs). Globally, RSV contributes to millions of LRTI cases annually, with a disproportionate burden in low- and middle-income countries (LMICs). The RSV virion outer capsule contains glycoproteins G and F which are essential for viral entry into respiratory epithelial cells and represent key targets for therapeutics development. The F-glycoprotein has several highly conserved antigenic sites that have proven useful targets for the development of monoclonal antibodies (mAbs) against RSV. Historically, prevention in infants was limited to the mAb palivizumab, which, despite its efficacy, was costly and inaccessible in many regions. Recent advancements include nirsevimab, a long-acting mAb that has shown substantial efficacy in reducing medically attended RSV-related disease in infants, in phase III clinical trials, early regional and national real-world data. In addition, three new vaccines have been approved: two protein subunit vaccines and a messenger RNA vaccine. The vaccines are all licenced for use in older adults, with one also approved as a maternal vaccine. Promising candidates in development include the mAb clesrovimab, which has an extended half-life and high levels in the nasal epithelial lining and high safety and efficacy profiles in late-stage trials. There are also a wide range of vaccine candidates currently in late-stage clinical trials. These developments signify a major advancement in RSV prevention strategies, offering improved protection for high-risk populations. With the ongoing rollout of the recently licenced vaccines and mAbs internationally, the landscape of RSV care is rapidly changing. We also must ensure these advances reach those in LMICs who need these therapies most.